Reconstruction of Integrative Islamic Education: An Interdisciplinary and Multidisciplinary Model in the Digital Era - Arna Saskia; Syukri Iska; Sri Fitra Oktrivia; Kumaidi Kumaidi; Muamar Aziz (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The development of digital technology has brought significant changes to Islamic education, requiring methodological and epistemological adaptations to maintain its relevance. The process of digitalizationmarked by the emergence of artificial intelligence, big data, and virtual learning environments has shifted the educational paradigm from traditional systems toward technology-based learning models. This study aims to reconstruct Islamic education studies through interdisciplinary and multidisciplinary approaches within the context of digitalization. The method employed is library research, involving the collection and analysis of literature from reputable journals, academic books, scientific articles, and relevant documents. The analysis was conducted descriptively and analytically using the Systematic Literature Review (SLR) method, which was chosen for its ability to provide structured, transparent, and replicable scientific evidence from various empirical research sources, thereby enabling learning to become more holistic and contextual. The databases selected were chosen for their reputation as high-quality sources encompassing numerous peer-reviewed scholarly journals. Meanwhile, the multidisciplinary approach strengthens cross-disciplinary collaboration in developing curricula and fostering innovation in digital-based learning. Furthermore, digitalization demands an epistemological reconstruction to ensure that Islamic values can continue to be internalized through modern technology.